New Approaches to Therapy of the Irritated Bowel Syndrome - N. V. Korochanskaya; G. A. Trembach (Медицинский вестник Юга России, 2012)
Purpose: To conduct a comparative analysis of the effectiveness of basic medical and comprehensive (basic and biofeedback therapy) treatment of IBS on the dynamics of clinical symptoms.Materials and Methods: In the current 2005 to 2009 study involved 75 women aged 18 to 40 years diagnosed with «Irritable bowel syndrome without diarrhea». The first group consisted of patients with IBS who received standard treatment (pinaveriya bromide, mebeverine hydrochloride, polifenilglikol, lactulose). Patients of the second group additionally received a course of biofeedback therapy on agriculture «INTEKS». The third group consisted of patients who have not completed a course biofeedback therapy.Results: No significant differences in clinical symptoms of disease in groups of patients with IBS before treatment were found. The best indicators were sick, conducted an additional course of biofeedback therapy.Summary: The combined therapy of IBS, consisting of standard medical therapy and biofeedback, has a higher efficiency in the long run, when the effect of a course of treatment is not symptomatic.